Instructional television programs in Egypt: a case study of the primary stage programs - Khalil, Mahitab (AUC Knowledge Fountain, 2010)
This study focuses on media for development; using television as a mass medium to serve education in Egypt. The study in hand is a case study concerned with the instructional television programs for the primary stage students in Egypt. The researcher focused on three pillars that are: education, media and more importantly, students and their parents. The study is guided by a learning system: Rich Environment for Active Learning. This system is based on the constructive theory that deals with learning as a life long experience. The learning process, thus, has to be joyful and engaging so that it makes sense to the students. If so, then the student too will intentionally seek information. The researcher conducted several in depth interviews and focus groups with representatives of the pillars. Moreover, the researcher carried on a discourse analysis for the primary stage instructional channels and programs for the six primary stage years. The findings show that the programs have some elements that make them appealing and engaging based on the REALs model and the standards identified by instructional and media experts. There is an effort exerted for producing a large number of programs annually. Yet, there are several problems that hold the programs back, such as the tight budget, lack of coordination and bureaucracy. Primary stage students lack the culture of active learning. The students and their parents are not aware of the programs, or they may watch them to memorize samples of questions expected to appear in the exams and their model answers. Students have to take private lessons. When the students watched a sample of the instructional programs and a sample of the Egyptian Sesame Street, for comparison, for them, Sesame Street was more popular, appealing, friendly and fun. While the instructional programs are perceived as old, classic, and if these two programs fight, Sesame Street will surely win.